Clinical and histological aspects of the anatomy of myopia, myopic macular degeneration and myopia-associated optic neuropathy - Jonas, Jost B.; Jonas, Rahul A.; Panda-Jonas, Songhomitra (Progress in retinal and eye research, 2025)
Axial myopia is characterized by a panoply of morphological, clinical and histological, features in association with longer axial length. It includes changes in the region peripheral to the optic nerve head (reduction in the density of photoreceptors and retinal pigment epithelium (RPE) cells and retinal thinning); in the optic nerve head region in moderately myopic eyes (shift of Bruch's membrane (BM) opening typically in the temporal/inferior direction, leading to a secondary BM overhang into the nasal intrapapillary compartment, BM absence in the temporal parapapillary region (“gamma zone”), and optic disc ovalization due to shortening of the ophthalmoscopically visible horizontal disc diameter; and widening of the RPE opening leading to myopic parapapillary beta zone), and in highly myopic eyes (BM opening enlargement resulting in a circular gamma zone, elongation and thinning of the lamina cribrosa (“secondary macrodisc”) and of the peripapillary scleral flange (“parapapillary delta zone”); and in the macular region with an elongation of the fovea-optic disc distance, reduction in angle kappa, straightening/stretching of the papillomacular retinal blood vessels and retinal nerve fibers (leading to a re-arrangement of the retinal nerve fibers with a myopia-specific regional distribution of the retinal nerve fiber layer thickness profile), choroidal thinning most pronounced at the posterior pole and affecting mainly the medium-sized and large choroidal vessel layer), and scleral thinning. Pathologic changes in the macular region are extrafoveally located, linear RPE layer defects (lacquer cracks), potentially widening to round RPE layer defects (patchy atrophies), in some eyes with central BM defects; BM defects with RPE layer defects in the foveal region, accompanied by macular neovascularization or subsequent subretinal RPE cell proliferation (“macular atrophy”); myopic macular retinoschisis; and staphylomas. With longer axial length, the prevalence of non-glaucomatous optic neuropathy and glaucoma-like/glaucomatous optic neuropathy steeply increases beyond an axial length of 26.0-26.5 mm. With BM thickness being independent of axial length and in view of eye shape change from an oblate or sphere in emmetropia to a prolate rotational ellipsoid in myopia, the myopia specific morphological changes may be associated with a primary BM enlargement in the region peripheral to the optic disc.